Location theory based wind energy system planning - Seng, Sue Men (2011)
Wind Energy is the one of the fastest growing renewable energy in the last two decades. Besides having the most rapid growth, wind energy has become a big part of the energy consumed globally. However, some of the key factors for a successful wind power project can be overlooked at times, leading to the failure of such projects and posing negative effects on its contribution. This project studies the key parameters that are crucial in the process of selecting potential location for optimal success in wind power planning at its initial stage. The aim is to build a model that can be generally applied during wind power planning. A multi-criteria decision making tool: Analytic Hierarchy Process (AHP) is implemented using Saaty scale ranging from 1-9 to form pairwise comparisons and evaluate the weightage of each criteria. The result shows the priorities of the parameters and their significance, indicating the order of which they should be carried out during planning process